From Mystical Unveiling to Spiritual Therapy: Kasyf and the Reconstruction of Sufi Healing in the Syadziliyah - Sauqi, Achmad (Tribakti: Jurnal Pemikiran Keislaman, 2026)
This article seeks to discuss of kasyf—the unveiling of inner truths—in the Syadziliyah Sufi healing practices of Tulungagung, Indonesia, focusing on santri experiences. Employing a phenomenological approach, data were gathered through observations and in-depth interviews with santri who have undergone kasyf. This article argues that kasyf significantly supports tazkiyatun nafs (self-purification) and enhances spiritual well-being. Notably, santri display differing levels of kasyf despite following the same zikir practices, highlighting its nature as a divinely bestowed experience rather than a structured objective. This sets Syadziliyah healing apart from other Sufi traditions, which often emphasize more systematic spiritual and psychological frameworks. The study also critiques Karim Mitha’s notion of “self-knowledge,” proposing “soul-knowledge”—an integrative framework combining self-knowledge and tazkiyatun nafs—to guide salik toward discovering the “true soul.” The research presents a novel model of transformative Sufi healing in the Syadziliyah tradition, emphasizing individualized spiritual experiences and the central role of divine grace in personal spiritual development.